Upaya Meningkatkan Kemampuan Passing Atas Pada Permainan Bolavoli Melalui Metode Discovery Pada Siswa Kelas X - Dali, Randi; Muda, Rudin; Paputungan, Andika; Syahril, Syahril; Prasasto, Angger Bagus; Hidayat, Joni Taufik; Ikhsan, Haerul; Ilham, Al (Universitas Negeri Gorontalo, 2025)
The problem in this study is the lack of upper passing ability in volleyball games in class X TAV students of SMK Negeri 1 Suwawa. The aim is to improve the learning process of physical education, sports and health through the application of the Discovery method, the aim is to improve students' ability to do upper passes in volleyball games taught at SMK Negeri 1 Suwawa. The increase in the ability to pass the upper ball through the discovery method in learning physical education, sports and health has exceeded the performance indicators set at 80%. This means that each cycle is very clear the difference in the increase, namely between the initial observation to cycle 1 the difference is 8.33 and cycle 1 to cycle 2 the difference is 37.04. Thus, the hypothesis in the classroom action research states that